Contribution of Iqbal's dynamic personality theory to Islamic psychology: a contrastive analysis with freud and selected mainstream western psychology - Mohd Abbas Bin Abdul Razak (Institute of Education, International Islamic University Malaysia, 2011)
The ever-changing paradigms in the West, pertaining to the study on man have caused much chaos and confusion in the minds of the masses not only in the West but also to a certain extent to the people in the East. This situation warrants the introduction of Islamic psychology, which provides a holistic and all encompassing explanation on man. The study has indicated that topics on human nature and personality theories are interrelated and therefore they are inseparable. The researcher has highlighted the fact that man, being a universe on the micro-level, has been constantly researched upon from the ancient to the modern times using philosophical as well as scientific approaches. On the whole, this study in the area of philosophical psychology is a contrastive analysis on the personality theories that have been showcased to the world by Freud and Iqbal. In analyzing the data pertinent to the study, the researcher has used the historical and content analysis methods. As a prelude to this endeavour, the researcher has explored the historical and philosophical developments that have taken place in the areas of human nature and personality in the West and the Islamic world. The researcher believes that the role of Islamic psychology as an 'arbitrator' can harmonize many of the ideas on man found within Western mainstream psychology. Through the contrastive analysis, it has come to light that Freud and Iqbal had conceptualized their theories on personality as a response to the demands and challenges of their time. Besides that, factors like their personality, philosophy towards life, education and their travels have influenced directly or indirectly their conceptualization of their theories. The study has indicated that all ideas said by Freud on human nature and personality are centered around his ideas on the human sexuality. His concept on human nature is one that is pessimistic and deterministic at the same time. To him, man is an intellectual beast who is doomed to fail as he is caught between the warring parties of his psychic components. But Iqbal, who had a strong Islamic background, promoted many positive ideas on man and on the latent powers of the human psyche. His theory of personality is not only dynamic in nature but inspires man to sink into his psyche to bring out all the latent positive aspects. Iqbal believed that by actualizing the hidden powers within man, he could transform this world into a better place for the benefit of all humanity. This act, in turn, will bring one in close contact with God. On the whole, his theory on personality gives man a dignified position as the vicegerent of God (Khalīfatullāh fī al-Ard) and a hope for a better world. The findings of the research have highlighted the fact that regardless of the latest development in the areas of human nature and personality development, the study on man will be a perennial one. Besides that, the findings have indicated that the least educationists can expect through the application of Freud's ideas on man in the field of education is to civilize the uncivilized part of his human nature. Conversely, the findings have also indicated that Iqbal's ideas on human nature and personality development are very much in line with the spirit of Islamization of Psychology. Moreover, his ideas on man which are dynamic in nature can yield positive results when applied in the fields of education, motivation, human capital development, leadership training, etc.